Welfare optimal reliability and reserve provision in electricity markets with increasing shares of renewable energy sources - Friðrik Már Baldursson; Julia Bellenbaum; Ewa Lazarczyk; Lenja Niesen; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance, 2017)
We develop an analytical model to derive the competitive market equilibrium for electricity spot and reserve markets under stochastic demand and uncertain renewable electricity generation. We then derive the welfare-optimal provision of reserves. At rst-best, cost of reserve capacity is balanced against expected cost of outages. The rst-best market equilibrium of the model implies an increase of reserve provision with a growing share of renewable generation. Furthermore, a growing share of renewable generation decreases the level of reliability as measured in energy not served. Additionally, required reserves to balance higher expected deviations will be more expensive, resulting in a trade-o between higher reserve costs and costs of energy not served.
Keywords: D81; L52; Q41; Q42; 330; Renewable Energy Sources; Electricity Reserves; Reliability; Electricity Market; TSO